HUBUNGAN KEPERCAYAAN DIRI DENGAN KEMANDIRIAN BELAJAR PESERTA DIDIK KELAS VIII A DAN VIII E DI SMPN 30 PADANG - Vidia Chairah; Yasrial Chandra; Joni Adison (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of self-confidence as a psychological factor influencing students’ learning independence. Self-confidence is believed to encourage students to become more active, initiative-driven, and responsible in the learning process. The purpose of this research is to examine the relationship between self-confidence and learning independence among students of classes VIII A and VIII E at SMP Negeri 30 Padang. The study employed a quantitative correlational design. The sample was determined using a total sampling technique. Data were collected through self-confidence and learning independence questionnaires that had been tested for validity and reliability. The data were analyzed using the Product Moment correlation technique. The results indicated that students’ self-confidence was categorized as fairly good, while learning independence was categorized as good. Correlation analysis revealed a positive and significant relationship between self-confidence and learning independence. These findings suggest that higher levels of self-confidence are associated with higher levels of learning independence. Therefore, teachers and schools are expected to implement learning strategies that foster students’ self-confidence to enhance their learning independence. Keywords: Self-Confidence, Learning Independence, Students